Cultural Education based Local Wisdom “Tradisi Tombor Magh” in Fak-Fak West Papua - Ferry Irawan; Dharma Gyta Sari Harahap; Muh. Rafi’y; Minuk Riyana; Cristiana Normalita de lima (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This article aims to examine one of the strategic efforts to preserve cultural values by orienting on a multicultural approach through cultural education based on local cultural values and principles to instill attitudes that show tolerance and uphold identity as a civilized local community so that The cultural values adhered to remain attached to the younger generation. Based on the results of qualitative phenomenological research and through structured interviews and observations on the indigenous people of Fak-Fak Regency, West Papua, the local wisdom of